Soy food intake and risk of gastric cancer: A dose–response meta-analysis of prospective studies. Issue 33 (August 2017) - Weng, Ke-Gui; Yuan, Ya-Ling
Abstract : Abstract: Epidemiological studies were inconsistent on the association between soy food intake and risk of gastric cancer (GC). This study aimed to determine the role of soy food intake in the development of GC. A systematic search was conducted in PubMed and Web of Science to identify all relevant studies. Study-specific relative risks (RRs) and 95% confidence intervals (CIs) were pooled using a random-effects model, and the dose–response relationship between soy food intake and GC risk was also assessed. Thirteen prospective studies were identified with a total of 517, 106 participants and 5800 cases. Among 11 types of soy food, high intake of total soy food (the highest vs the lowest category: RR: 0.78, 95% CI: 0.62–0.98) and nonfermented soy food (RR: 0.63, 95% CI: 0.50–0.79) were inversely associated with GC risk, while high intake of miso soup was associated with the risk in male (RR: 1.17, 95% CI: 1.02–1.36). In dose–response meta-analysis, total soy food intake (0–150 g/day) showed no significant association with GC risk, while high intake of nonfermented soy food was inversely related, especially an intake of more than 100 g/day. In male, miso soup intake (1–5 cups/day) was significantly associated with GC risk. High intake of nonfermented soy food might reduce the risk of GC, while miso soup intake might increase the risk in male.